2020
DOI: 10.1177/0954406220908623
|View full text |Cite
|
Sign up to set email alerts
|

A novel pulse-adaption flow control method for a turbocharger turbine: Elastically restrained guide vane

Abstract: A turbocharger is a key enabler for energy conservation in an internal combustion engine. The turbine in a turbocharger is fed by highly pulsating gas flow due to the reciprocating engine, resulting in significant deterioration of the turbocharger performance. To solve this problem, a novel pulse-optimized regulation mechanism named ‘elastically restrained guide vane’ for a novel variable geometry turbocharger is proposed in this paper. The new mechanism regulates the instantaneous flow angle at turbine inlet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Overall, the test and simulation of the swallowing capacity were in good agreement with each other and had a maximum error value of 2.62% at the speed of 150,000 rpm, which was within the acceptable range. This discrepancy was attributed to the simplification of the secondary feature in the geometry, the parameter settings for heat transfer in the simulation, and a manufacturing error [45,46]; moreover, it could be influenced by the optimal application scope of the SST model [47].…”
Section: Model Validationmentioning
confidence: 99%
“…Overall, the test and simulation of the swallowing capacity were in good agreement with each other and had a maximum error value of 2.62% at the speed of 150,000 rpm, which was within the acceptable range. This discrepancy was attributed to the simplification of the secondary feature in the geometry, the parameter settings for heat transfer in the simulation, and a manufacturing error [45,46]; moreover, it could be influenced by the optimal application scope of the SST model [47].…”
Section: Model Validationmentioning
confidence: 99%
“…In the recent papers, 9,10 we proposed a novel self-adaptive regulation mechanism named “elastically restrained guide vane (ERGV)” for the turbocharger turbine inlet to simplify the complex regulatory mechanism of the traditional VGT, thereby reducing the cost and allowing the replacement of standard VGT under some special situations. The ERGV is a special type of VGT.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of this developed secondary flow injection system which allowed a 24% increase in the output torque, a further study is needed on this injection system taking into account the actual thermodynamic properties of the engine combustion products. Wang et al 16 suggested a novel system, so-called elastically restrained guide vane, as a replacement of the classical vane mechanism of VGT turbines. They modeled their system with a set of fluid-structure interaction simulations.…”
Section: Introductionmentioning
confidence: 99%